Persistent Room Temperature Phosphorescence from Triarylboranes: A Combined Experimental and Theoretical Study. (4th August 2020) - Wu, Zhu; Nitsch, Jörn; Schuster, Julia; Friedrich, Alexandra; Edkins, Katharina; Loebnitz, Marcel; Dinkelbach, Fabian; Stepanenko, Vladimir; Würthner, Frank; Marian, Christel M.; Ji, Lei; Marder, Todd B.
Abstract: Achieving highly efficient phosphorescence in purely organic luminophors at room temperature remains a major challenge due to slow intersystem crossing (ISC) rates in combination with effective non‐radiative processes in those systems. Most room temperature phosphorescent (RTP) organic materials have O‐ or N‐lone pairs leading to low lying (n, π*) and (π, π*) excited states which accelerate k isc through El‐Sayed's rule. Herein, we report the first persistent RTP with lifetimes up to 0.5 s from simple triarylboranes which have no lone pairs. RTP is only observed in the crystalline state and in highly doped PMMA films which are indicative of aggregation induced emission (AIE). Detailed crystal structure analysis suggested that intermolecular interactions are important for efficient RTP. Furthermore, photophysical studies of the isolated molecules in a frozen glass, in combination with DFT/MRCI calculations, show that (σ, B p)→(π, B p) transitions accelerate the ISC process. This work provides a new approach for the design of RTP materials without (n, π*) transitions. Abstract : Efficient intersystem crossing (ISC) in combination with strong intermolecular interactions suppresses the nonradiative decay rate k nr and leads to the first reported persistent room temperature phosphorescence (RTP) from purely organic triarylborane phosphors, which do not possess O‐ or N‐lone pairs. Transitions between local σ‐ and π‐excitation also accelerate k isc .